Epigenetics and aging - Mellor, J (2010)
Aging is the accumulation of changes in an organism over time that leads to reduced viability. Studies in model organisms indicate that aging is genetically determined and that alterations to specific genes can extend or shorten lifespan. Some organisms exhibit negligible aging with no loss of metabolic functions or fertility over time, despite a high metabolic rate, raising the question as to why and how some organisms age and die. A number of theories of aging have been proposed, including telomere shortening, wear and tear (somatic mutations, error accumulation, loss of protein function, etc.), autoimmune disease and reduced mitochondrial function leading to oxidative stress and damage to DNA and proteins1. © 2010 The Biochemical Society.